Ecolexicons in Conservation News Text in Mass Media: Ecolinguistics - Yuniawan, Tommi; Rokhman, Fathur; Rustono, Rustono; Bakti Mardikantoro, Hari (The Journal of Educational Development, 2018)
Conservation news texts contain the expression of language on conservation events or issues presented based on arguments related to the vision of the university (Universitas Negeri Semarang) with conservation. Conservation is an important and sensitive issue for the community. This is because it is commonly associated with institutional policy or ideology. The purpose of this study is to describe the form of ecolexicon in conservation text in mass media. The theoretical framework used is ecolinguistics. Then, the data used is a conservation news text containing ecolexicon. The data source is from the mass media at webpage www.unnes.ac.id which has relatively a large number of text data of conservation so that the data will be more varied. Method of data collection is done by employing simak method, literature study method, and documentation method. Furthermore, the data were analyzed by ecolinguistic study using the method of padan and agih. Based on data analysis, it is found that ecolexicon forms are found in the conservation news text, i.e., basic words, derivative words, phrases, and expression. The ecolexicon forms found in the conservation news text can be classified into two types of referents, i.e. biotic references (flora/fauna) and abiotic referents. The results of this study can contribute theoretically and practically in the field of linguistics, language learning, journalism, and public policy. For this reason, the study of ecolinguistics in conservation news text in the mass media deserves to be given space as a form of prospective eco-linguistic analysis.